Os efeitos da adoção monoparental realizada por casais homoafetivos à luz dos direitos humanos fundamentais rizomáticos - Pertel, Adriana Maria dos Santos (2012)
The problematization of this research starts from the following questions: How effective the fundamental right of membership of the single parent adoption when in fact adopted the factual lives in a family homo affective? The argument that this condition violates the access of children and adolescents for fundamental human rights rhizomatic, enabling joint justified by homosexual couples? The objective of the research is to demonstrate that the changes in family law occur on the fringes of society with its own evolutionary framework connected to the development of man and society, becomes according to the new achievements of mankind, being a living reality that needs arguably the attention of law enforcement officers, so that they can gain legitimacy in the judiciary, since the law cannot keep up social facts. The methodology used to demonstrate the denial of the rights inherent in membership to children and adolescents adopted in a single parent was the multiple dialectical because it allowed a multidisciplinary approach between the sciences and mainly allowed comparing the arguments used by the Judiciary and Prosecutors to reject requests enabling joint peer homosexual. We need to realize that government authorities to enforce rights arising from membership of children living in a home homo affective where the adoption occurred Parent is essential that actions are multidisciplinary, cross, this is, not only restricted the science of law, but which also dialogue with other sciences such as sociology, philosophy and psychology. Recognizing the primacy of the principle of the best interests of the child and adolescent. Thus we seek to invoke the emergence of a membership socioaffective, modern institute that is recognized as a generator of parental bonding, having priority over biological reality. Finally, the analysis suggests, the perspective presented theoretical and legal cases that involve judicial recognition of joint adoptions by homosexual couples who have already been judged by the higher Courts of the National Judiciary.